2021
DOI: 10.4103/ajns.ajns_380_20
|View full text |Cite
|
Sign up to set email alerts
|

Rapid spontaneous resolution of the acute subdural hematoma: Case series and review of literature

Abstract: Background: Traumatic acute subdural hematoma (ASDH) is an oft encountered entity in neurosurgery. While resolution of such thick SDHs usually takes time, certain cases of rapid spontaneous resolution have also been reported. This article attempts to review the pathophysiology, clinical and radiological features of such cases, as well as provide an insight into decision making for their management. Methods: Electronic literature search was done to look for similar cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…Spontaneous resolution in a short period is known to be an infrequent but distinct phenomenon of ASDH, which is represented by dissemination and redistribution of the subdural hematoma. [10] In addition, the period for the transformation of the ASDH into the symptomatic CSDH in our case was consistent with that seen in previous study. [5] Although not evident on neuroimages, intraoperative and histological findings showed that the nodular lesion presented microvascular proliferation, typically a characteristic finding of the outer membrane of CSDHs, indicating production of hematoma fluid.…”
Section: Discussionsupporting
confidence: 92%
“…Spontaneous resolution in a short period is known to be an infrequent but distinct phenomenon of ASDH, which is represented by dissemination and redistribution of the subdural hematoma. [10] In addition, the period for the transformation of the ASDH into the symptomatic CSDH in our case was consistent with that seen in previous study. [5] Although not evident on neuroimages, intraoperative and histological findings showed that the nodular lesion presented microvascular proliferation, typically a characteristic finding of the outer membrane of CSDHs, indicating production of hematoma fluid.…”
Section: Discussionsupporting
confidence: 92%
“…Although the true incidence of rapid spontaneous resolution or redistribution of ASDH is unknown, it can occur very rarely. 7 12 17 19) Rathore et al 12) have reviewed their 5 cases of rapid spontaneous resolution of ASDH within 72 hours and 39 such cases reported previously. In their review, radiological findings of resolution of ASDH or clot reduction started at 1 hour after trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In their review, radiological findings of resolution of ASDH or clot reduction started at 1 hour after trauma. 12) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all head traumas from mild to severe, an average of 11% is complicated by an acute SDH [ 4 , 6 ]. Patients with an acute SDH present with symptoms ranging from their neurological baselines to varying levels of consciousness to coma [ 7 ]. Interestingly, focal deficits may be ipsilateral or contralateral to the side of the SDH [ 8 ].…”
Section: Introductionmentioning
confidence: 99%